2015
DOI: 10.1186/s13054-015-0741-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx and sepsis-induced alterations in vascular permeability

Abstract: Endothelial cells line the inner portion of the heart, blood vessels, and lymphatic vessels; a basal membrane of extracellular matrix lines the extraluminal side of endothelial cells. The apical side of endothelial cells is the site for the glycocalyx, which is a complex network of macromolecules, including cell-bound proteoglycans and sialoproteins. Sepsis-associated alterations of this structure may compromise endothelial permeability with associated interstitial fluid shift and generalized edema. Indeed, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
256
3
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(279 citation statements)
references
References 73 publications
1
256
3
14
Order By: Relevance
“…This conclusion is further supported by the finding that SDX has a beneficiary effect in the LPS-induced model of sepsis, which bypasses micro-organismal installation. On the other hand, a significant increase in sepsisrelated vascular permeability (Chelazzi et al, 2015) is curtailed by SDX. Although SDX is credited with anti-inflammatory and antithrombotic actions (Hoppensteadt and Fareed, 2014), it is likely that correction of vascular permeability is related to the It has been previously demonstrated that glycocalyx of endothelial cells and erythrocytes is impaired in the in vitro flow system when one of the cellular components has lost glycocalyx integrity (Oberleithner, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is further supported by the finding that SDX has a beneficiary effect in the LPS-induced model of sepsis, which bypasses micro-organismal installation. On the other hand, a significant increase in sepsisrelated vascular permeability (Chelazzi et al, 2015) is curtailed by SDX. Although SDX is credited with anti-inflammatory and antithrombotic actions (Hoppensteadt and Fareed, 2014), it is likely that correction of vascular permeability is related to the It has been previously demonstrated that glycocalyx of endothelial cells and erythrocytes is impaired in the in vitro flow system when one of the cellular components has lost glycocalyx integrity (Oberleithner, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…55 Another emerging possibility to act therapeutically on endothelial vascular integrity involves Toll-like receptor 4-dependent activation of endothelial cells 56 and modulation thrombomodulindriven pathways. 57 From the long-term perspective, postinsult recovery of the peritubular capillary network may prevent chronic tubulointestinal hypoxia and fibrosis.…”
Section: Targets To Protect the Nephrovascular Unitsmentioning
confidence: 99%
“…Vienas pagrindinių veiksnių, sukeliančių šį skirtumą -sepsio metu aktyvintų uždegiminių ir priešuždegiminių mediatorių, bakterijų endotoksinų sukeltas endotelio pažeidimas ir glikokalikso vientisumo pažeidimas. Šis pažeidimas sukelia endotelio pralaidumą ir su tuo susijusį skysčių persiskirstymą bei intersticinės edemos formavimąsi [7]. Patologinį skysčio perėjimą sukelia ne tik minėtas mechanizmas, bet ir operacijos metu atliekamos chirurginės manipuliacijos, didinančios baltymų perėjimą iš kraujagyslės į tarpląstelinį tarpą, reperfuzinė pažaida, silpninanti kraujagyslinį barjerą, bei jatrogeninė hipervolemija, galinti sukelti glikokalikso pažeidimą, dėl kurio skysčiai ir baltymai pereina į ekstravaskulinį tarpą [8].…”
Section: įVadasunclassified